Investigation of relationship between newly imposed requirements for daylight factor in DS/EN 16798 and energy use in office buildings designed according to Danish building class 2020 - Miguel, Marco António Sousa (2017)
Tese de mestrado integrado, Engenharia da Energia e do Ambiente, Universidade de Lisboa, Faculdade de Ciências, 2017